Seven Years Single Center Experience of Combined Coronary Artery Bypass Surgery with Aortic Valve Replacement: retrospective cohort Study - Gautam, Navin Chandra; Joshi, Rheecha; Panthee, Nirmal; Bohara, Sujan; Gautam, Ashima; Chaudhary, Aashutosh (Nepalese Heart Journal, 2025)
Background and aims: Combined coronary artery bypass graft (CABG) with aortic valve replacement (AVR) surgery (CABG-AVR) is considered high-risk compared with isolated CABG and AVR. This study aims to report on a seven-year single-center experience of the outcome of combined CABG-AVR surgery. Methods: This is a retrospective review of institutional data from July 2016 to June 2023. All elective cases of concomitant CABG-AVR surgery were included. The preoperative, intraoperative, postoperative, mortality before discharge, and early and late mortality data were collected and then analyzed in R 4.4.2. Software. Results: A total of forty-three patients underwent CABG-AVR surgery in seven years, out of which 9 (20.93%) were female. The mean age (in years) was 61.37 ± 10.09. The mean left ventricular ejection fraction (%) was 55.58 ± 10.07. Twenty-six had severe aortic stenosis, eight had severe aortic regurgitation, and nine had a mixed lesion. Ten of these had triple vessel disease (VD), 16 had double VD, and 17 had single VD. The mean postoperative intensive care unit stay was 4.65+4.80 days, and the mean postoperative hospital stay was 8.47+6.06 days. In-hospital mortality was 4 (9.3%) patients. The maximum follow-up was 98 months, and the minimum follow-up for two months, with a mean follow-up of 35 months. The follow-up was completed by 93%. The cumulative survival rate at 8.1 years was 0.73 (CI: 0.56-0.94). Conclusion: Although small sample size may limit statistical significance for some analysis, this study suggests that combined CABG-AVR surgery can be performed with acceptable outcomes in our context.